A heat-sealable BOPP film for cigarettes and preparation method thereof
By using nano-scale etching of tourmaline in the BOPP film for heat-sealed smoke, the problem of insufficient gloss is solved, and the gloss is improved and various performances is improved.
Patent Information
- Application Number
- CN202411100694.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-08-12
AI Technical Summary
The existing BOPP films for heat sealed smoke are low in crystal integrity due to modification, which makes it easy to refract or reflect light, making it difficult to meet the needs of gloss.
By using nanoscale etched tourmaline, the optical performance of the film is optimized, transparency and gloss is improved, and the particle size and weight ratio of the etched tourmaline and the unetched tourmaline are adapted to different application environments.
The glossiness of the BOPP film for smoke is improved, the physical properties and appearance quality of the film are enhanced, and the anti-static, friction and heat sealing properties are improved.
Smart Images

Figure BDA0004989287210000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of BOPP films, in particular to a heat-sealed BOPP film for cigarettes and a preparation method thereof. Background Art
[0002] Biaxially oriented polypropylene (BOPP) film is characterized by light weight, transparency, non-toxicity, moisture resistance, low air permeability, and high mechanical strength. It is widely used in food, clothing, medicine, chemical industry and other fields. BOPP film can be multi-layered with polypropylene cast film, polyethylene film, polyvinyl alcohol film, etc., so as to improve the gas barrier, moisture barrier, oil resistance and tear resistance of the product. It is a packaging material that has developed rapidly in recent years. Cigarette film is a high-grade BOPP film with the characteristics of low heat sealing temperature, good barrier performance, high transparency and uniform thickness.
[0003] For example, the Chinese patent, application number CN202110419090.8, is a heat-sealable BOPP film for cigarettes, which is made by direct co-extrusion of a three-layer structure of an outer layer, an interlayer, and an inner layer; the outer layer is made of the following raw materials in parts by weight: 38-45 parts of random copolymer polypropylene, 20-26 parts of propylene-ethylene copolymer, 25-32 parts of ethylene-methyl acrylate copolymer, 7.5-9 parts of modified crystalline tourmaline powder, 1.5-2 parts of 1,6-hexanediol diglycidyl ether, 4.6-5.2 parts of a mixture of trimethylsiloxyamino-terminated polydimethylsiloxane and hydroxy-terminated methyl-3,3,3-trifluoropropyl polysiloxane, and 3-4.5 parts of polytetrafluoroethylene modified polyethylene wax powder; the interlayer is made of the following raw materials in parts by weight: 80-90 parts of homopolymer polypropylene, 12-17 parts of propylene-ethylene copolymer, 7-9 parts of ethylene-methyl acrylate copolymer, and 2-3 parts of nano silicon dioxide. The heat-sealed BOPP film for cigarettes of the invention has small static / dynamic friction coefficient, good and lasting antistatic effect, good low-temperature heat-sealing performance and excellent comprehensive performance.
[0004] However, due to the low integrity of the crystal caused by its modification, it is easy to refract or reflect light, resulting in its glossiness failing to meet the requirements. Summary of the invention
[0005] The embodiments of the present application provide a heat-sealable BOPP film for cigarettes and a preparation method thereof, thereby solving the problem in the prior art that the modification causes crystals to easily produce refraction or reflection, resulting in a decrease in gloss, and achieving an improvement in the gloss of the BOPP film for cigarettes.
[0006] The embodiment of the present application provides a heat-sealable BOPP film for cigarettes, which is specifically made by direct co-extrusion of a three-layer structure of an outer layer, an intermediate layer, and an inner layer;
[0007] Wherein, the outer layer is made of raw materials including the following parts by weight:
[0008] 38-45 parts of polypropylene, 20-26 parts of propylene-ethylene copolymer, 25-32 parts of ethylene-methyl acrylate copolymer, 7.5-9 parts of etched crystal tourmaline powder, 1.5-2 parts of 1,6-hexanediol diglycidyl ether, 4.6-5.2 parts of a mixture of trimethylsiloxyamino-terminated polydimethylsiloxane and hydroxyl-terminated methyl-3,3,3-trifluoropropyl polysiloxane, and 3-4.5 parts of polytetrafluoroethylene etched polyethylene wax powder;
[0009] The interlayer is made of the following raw materials in parts by weight:
[0010] Polypropylene 80-90 parts, propylene-ethylene copolymer 12-17 parts, ethylene-methyl acrylate copolymer 7-9 parts;
[0011] The inner layer is made of the following raw materials in parts by weight:
[0012] 38-45 parts of polypropylene, 20-26 parts of propylene-ethylene copolymer, 25-32 parts of ethylene-methyl acrylate copolymer;
[0013] The etched crystalline tourmaline powder is prepared by etching crystalline tourmaline powder; the particle size of the crystalline tourmaline powder is 20-100nm;
[0014] The thickness of the outer layer and the inner layer is 0.8-1.2 μm, and the thickness of the interlayer is 18-22 μm.
[0015] Furthermore, the interlayer also includes 2-3 parts of nano silicon dioxide.
[0016] Furthermore, the outer layer also includes 2-3 parts of nano silicon dioxide.
[0017] Furthermore, the interlayer also includes 10-12 parts of crystalline tourmaline powder.
[0018] Furthermore, the inner layer also includes 3-5 parts of crystalline tourmaline powder.
[0019] Furthermore, the crystalline tourmaline powder of the interlayer is etched crystalline tourmaline powder.
[0020] Furthermore, the crystalline tourmaline powder of the interlayer is a mixture of etched crystalline tourmaline powder and unetched crystalline tourmaline powder.
[0021] Furthermore, the particle size of the unetched crystalline tourmaline powder is 150-350nm; the particle size of the etched crystalline tourmaline powder is 20-100nm, and the mass ratio of the unetched crystalline tourmaline powder to the etched crystalline tourmaline powder is 1:1.
[0022] Furthermore, the particle sizes of the etched crystal tourmaline powder contained in the interlayer are divided into large particle size of 200-400nm, medium particle size of 100-200nm, and small particle size of 20-100nm;
[0023] The particle sizes of unetched crystalline tourmaline powder are divided into large particle size 200-400nm, medium particle size 100-200nm, and small particle size 20-100nm;
[0024] The weight ratio of etched crystal tourmaline powder to unetched tourmaline powder is 1:(3-5) for high gloss, (1-2) for balance, (1-2) for high stability, (3-5) for high stability.
[0025] The combination of the particle size and weight ratio of etched crystal tourmaline powder and unetched tourmaline powder can be used to adapt to different application environments.
[0026] The method for preparing the heat-sealable BOPP film for cigarettes comprises the following steps:
[0027] S1, preparing etched crystalline tourmaline powder, specifically adding concentrated sulfuric acid in an amount of 1.2-1.5 times the mass of the crystalline tourmaline powder to the crystalline tourmaline powder, stirring the reaction for 10-15 minutes, controlling the concentration of sulfuric acid to be greater than 95% during the entire reaction process, and controlling the temperature during the entire reaction process to be 50° C.; filtering after the reaction is completed, washing the filter residue with water and drying it in turn, to obtain the etched crystalline tourmaline powder;
[0028] S2, preparing a mixture of the outer layer raw materials, specifically, drying the etched crystal tourmaline powder until the moisture content is less than 0.2wt%, then mixing the dried etched crystal tourmaline powder with 1,6-hexanediol diglycidyl ether, and placing it at 52-60°C and 2-3 standard atmospheric pressures for 6-10 hours; and then mixing it with a mixture of trimethylsiloxyamino-terminated polydimethylsiloxane and hydroxyl-terminated methyl-3,3,3-trifluoropropyl polysiloxane to obtain an etched crystal tourmaline powder premix;
[0029] S3, preparing melts of each layer: uniformly mixing the etched crystal tourmaline powder premix with other raw materials of the outer layer, melting and plasticizing, to form an outer layer melt;
[0030] The raw materials of the interlayer and the inner layer are mixed evenly, melted and plasticized to form an interlayer melt;
[0031] S4, the interlayer melt, the outer layer melt and the inner layer melt are extruded after being merged at the die head, and are rapidly cooled by a quenching roller and a water tank to form a solid casting sheet; then longitudinal stretching and transverse stretching are performed; and cooling and shaping treatment is immediately performed after stretching;
[0032] S5, sequentially undergoing online thickness measurement, edge material cutting, automatic winding, aging treatment, and finally slitting to obtain the finished product, the heat-sealed BOPP film for cigarettes.
[0033] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:
[0034] First, nano-scale etched crystal tourmaline powder has a smaller particle size and better dispersibility in the polymer matrix, achieving a more uniform film structure and improving the physical properties and appearance quality of the film; due to its small size, nanoparticles are more likely to form a stronger interface interaction with the polymer matrix, improving the mechanical properties and thermal stability of the film; the scattering and absorption of light by nanoparticles is different from that of large particles. The use of nano-scale crystal tourmaline powder optimizes the optical properties of the film, such as transparency and gloss, and due to the refinement of the particles, the dispersion is more uniform during melting, reducing the haze;
[0035] Second, nano-scale crystalline tourmaline powder is easier to be evenly dispersed during the melting and plasticizing process, which improves the processing performance of the film and makes the extrusion and stretching processes smoother; nanoparticles are more likely to form a continuous network in the film, so that macromolecular polymers can not only be loaded on the etched nano-crystalline tourmaline powder, but also cross-linked with each other to form a more stable structure;
[0036] Third, the microporous structure of etched crystal tourmaline powder plays a vital role in the preparation of heat-sealable BOPP film for cigarettes. By optimizing the formation conditions of the microporous structure and the anchoring effect of additives, the key indicators of the film such as friction performance, antistatic performance, heat sealing performance and mechanical properties can be significantly improved.
[0037] Fourthly, by adjusting the particle size and weight ratio of etched crystalline tourmaline powder and unetched crystalline tourmaline powder, it can flexibly adapt to different application environments; the stability and dispersibility of etched tourmaline powder and the natural properties of unetched tourmaline powder are comprehensively utilized to improve the overall performance of the cigarette film. DETAILED DESCRIPTION
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.
[0039] Embodiment 1
[0040] The present application includes a heat-sealable BOPP film for cigarettes, which is specifically made by direct co-extrusion of a three-layer structure of an outer layer, an intermediate layer, and an inner layer;
[0041] Wherein, the outer layer is made of raw materials including the following parts by weight:
[0042] 38-45 parts of polypropylene, 20-26 parts of propylene-ethylene copolymer, 25-32 parts of ethylene-methyl acrylate copolymer, 7.5-9 parts of etched crystal tourmaline powder, 1.5-2 parts of 1,6-hexanediol diglycidyl ether, 4.6-5.2 parts of a mixture of trimethylsiloxyamino-terminated polydimethylsiloxane and hydroxyl-terminated methyl-3,3,3-trifluoropropyl polysiloxane, and 3-4.5 parts of polytetrafluoroethylene etched polyethylene wax powder;
[0043] The interlayer is made of the following raw materials in parts by weight:
[0044] 80-90 parts of polypropylene, 12-17 parts of propylene-ethylene copolymer, 7-9 parts of ethylene-methyl acrylate copolymer, 2-3 parts of nano-silicon dioxide;
[0045] The inner layer is made of the following raw materials in parts by weight:
[0046] 38-45 parts of polypropylene, 20-26 parts of propylene-ethylene copolymer, 25-32 parts of ethylene-methyl acrylate copolymer, 3-5 parts of crystalline tourmaline powder;
[0047] The particle size of the crystal tourmaline powder is 20-100nm; the etched crystal tourmaline powder is made by etching the crystal tourmaline powder;
[0048] The thickness of the outer layer and the inner layer is 0.8-1.2 μm, and the thickness of the interlayer is 18-22 μm;
[0049] The method for preparing the heat-sealable BOPP film for cigarettes comprises the following steps:
[0050] S1, preparing etched crystalline tourmaline powder, specifically adding concentrated sulfuric acid in an amount of 1.2-1.5 times the mass of the crystalline tourmaline powder to the crystalline tourmaline powder, stirring the reaction for 10-15 minutes, controlling the concentration of sulfuric acid to be greater than 95% during the entire reaction process, and controlling the temperature during the entire reaction process to be 50° C.; filtering after the reaction is completed, washing the filter residue with water and drying it in turn, to obtain the etched crystalline tourmaline powder;
[0051] S2, preparing a mixture of the outer layer raw materials, specifically, drying the etched crystal tourmaline powder until the moisture content is less than 0.2wt%, then mixing the dried etched crystal tourmaline powder with 1,6-hexanediol diglycidyl ether, and placing it at 52-60°C and 2-3 standard atmospheric pressures for 6-10 hours; and then mixing it with a mixture of trimethylsiloxyamino-terminated polydimethylsiloxane and hydroxyl-terminated methyl-3,3,3-trifluoropropyl polysiloxane to obtain an etched crystal tourmaline powder premix;
[0052] S3, preparing melts of each layer: uniformly mixing the etched crystal tourmaline powder premix with other raw materials of the outer layer, melting and plasticizing, to form an outer layer melt;
[0053] The raw materials of the interlayer and the inner layer are mixed evenly, melted and plasticized to form an interlayer melt;
[0054] S4, the interlayer melt, the outer layer melt and the inner layer melt are extruded after being merged at the die head, and are rapidly cooled by a quenching roller and a water tank to form a solid casting sheet; then longitudinal stretching and transverse stretching are performed; and cooling and shaping treatment is immediately performed after stretching;
[0055] S5, sequentially undergoing online thickness measurement, edge material cutting, automatic winding, aging treatment, and finally slitting to obtain the finished product, the heat-sealed BOPP film for cigarettes.
[0056] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0057] Nano-scale etched crystal tourmaline powder has a smaller particle size and better dispersion in the polymer matrix, achieving a more uniform film structure and improving the physical properties and appearance quality of the film; due to its small size, nanoparticles are more likely to form a stronger interface interaction with the polymer matrix, improving the mechanical properties and thermal stability of the film;
[0058] Nano-scale crystalline tourmaline powder is easier to be evenly dispersed during the melt plasticization process, which improves the processing performance of the film and makes the extrusion and stretching processes smoother; nanoparticles are more likely to form a continuous network in the film, so that macromolecular polymers can not only be loaded on the etched nano-crystalline tourmaline powder, but also cross-linked with each other to form a more stable structure;
[0059] Nanoparticles have different scattering and absorption effects on light than large particles. Nano-scale crystalline tourmaline powder is used to optimize the optical properties of the film, such as transparency and glossiness. Due to the refinement of the particles, the dispersion is more uniform during melting, reducing the haze.
[0060] And due to the refinement of particles, the surface of BOPP film is smoother, the friction coefficient is further reduced, and it is less affected by temperature, making its packaging speed faster;
[0061] Nano-crystalline tourmaline powder has the ability to release negative ions, which greatly reduces static electricity and lasts for a long time.
[0062] Embodiment 2
[0063] The above embodiment improves the stability of the BOPP film by using smaller crystalline tourmaline powder and etched crystalline tourmaline powder, and also improves its transmittance and glossiness and reduces haze. In order to improve its heat sealing effect, etched crystalline tourmaline powder is also added to the interlayer, and further improvements are made on the basis of Example 1.
[0064] The outer layer also includes 2-3 parts of nano silicon dioxide;
[0065] In the interlayer, 10-12 parts of etched crystal tourmaline powder are used to replace nano silicon dioxide;
[0066] That is, the interlayer is made of the following raw materials in parts by weight:
[0067] 80-90 parts of polypropylene, 12-17 parts of propylene-ethylene copolymer, 7-9 parts of ethylene-methyl acrylate copolymer, 10-12 parts of etched crystal tourmaline powder;
[0068] The outer layer is made of the following raw materials in parts by weight:
[0069] 38-45 parts of polypropylene, 20-26 parts of propylene-ethylene copolymer, 25-32 parts of ethylene-methyl acrylate copolymer, 7.5-9 parts of etched crystal tourmaline powder, 1.5-2 parts of 1,6-hexanediol diglycidyl ether, 4.6-5.2 parts of a mixture of trimethylsiloxyamino-terminated polydimethylsiloxane and hydroxyl-terminated methyl-3,3,3-trifluoropropyl polysiloxane, 3-4.5 parts of polytetrafluoroethylene etched polyethylene wax powder, and 2-3 parts of nano silicon dioxide;
[0070] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0071] Etched crystal tourmaline powder has excellent antistatic properties. Adding etched crystal tourmaline powder to the middle layer of BOPP film can reduce the static electricity generated by the film and improve the antistatic effect of the film, making the film more stable during use and less likely to absorb dust or generate static electricity discharge. The etched crystal tourmaline powder is wrapped inside the film, which can effectively avoid direct wear, corrosion or pollution caused by the external environment, thereby extending the functional life of the tourmaline powder and the overall durability of the film. It also makes it easier for the etched crystal tourmaline powder to be evenly distributed in the film, improving the overall performance of the film and more evenly affecting the structure and performance of the entire film material.
[0072] Nano-silicon dioxide has a high specific surface area and a small size effect. Adding it to the outer layer of BOPP film can significantly improve the mechanical properties of the film, making the film more durable and less prone to damage when subjected to external forces. It can also improve the oxygen barrier properties of the material, reduce the amount of oxygen that penetrates the film into the packaging, thereby extending the service life and making the film and cigarette box fit more closely. Under high temperature conditions, many plastic films will change color, deform, and become brittle. The addition of nano-silicon dioxide can significantly improve the heat resistance of BOPP film, allowing it to maintain stable physical and chemical properties under high temperature conditions. The addition of nano-silicon dioxide can also improve the surface gloss of BOPP film.
[0073] Embodiment 3
[0074] In Example 2, etched crystal tourmaline powder is added to the interlayer and nano-silicon dioxide is moved to the outer layer to improve its antistatic ability, and also improve the overall durability and surface gloss. In order to improve its heat sealing ability, the crystal tourmaline powder of the inner layer is moved to the interlayer, which is further improved on the basis of Example 2.
[0075] No more crystal tourmaline powder is added to the inner layer;
[0076] The etched crystal tourmaline powder added to the interlayer includes two crystal tourmaline powders with different etching depths, and a coupling agent 1,6-hexanediol diglycidyl ether is added;
[0077] That is, the interlayer is made of the following raw materials in parts by weight:
[0078] 80-90 parts of polypropylene, 12-17 parts of propylene-ethylene copolymer, 7-9 parts of ethylene-methyl acrylate copolymer, 5-6 parts of shallowly etched crystalline tourmaline powder, 5-6 parts of deeply etched crystalline tourmaline powder, 0.5-1 part of 1,6-hexanediol diglycidyl ether;
[0079] The preparation method of lightly etched crystalline tourmaline powder is specifically as follows: adding concentrated sulfuric acid of 1.2-1.5 times the mass of the crystalline tourmaline powder to the crystalline tourmaline powder, stirring and reacting for 0.5-3 minutes, the concentration of the sulfuric acid is greater than 95%, and the temperature during the reaction is 50°C;
[0080] The preparation method of deep-etched crystalline tourmaline powder is specifically as follows: adding concentrated sulfuric acid of 1.2-1.5 times the mass of the crystalline tourmaline powder to the crystalline tourmaline powder, stirring and reacting for 10-25 minutes, the concentration of the sulfuric acid is greater than 95%, and the temperature during the reaction is 50°C;
[0081] The inner layer is made of the following raw materials in parts by weight:
[0082] 38-45 parts of polypropylene, 20-26 parts of propylene-ethylene copolymer, 25-32 parts of ethylene-methyl acrylate copolymer;
[0083] The shallow etched crystal tourmaline powder and the deep etched crystal tourmaline powder are pre-treated before being added to the interlayer, and the shallow etched crystal tourmaline powder and the deep etched crystal tourmaline powder are mixed and 1,6-hexanediol diglycidyl ether is added;
[0084] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0085] 1,6-Hexanediol diglycidyl ether as a coupling agent can effectively form a bridge between shallow etching particles and deep etching particles, enhancing the interfacial bonding between them. This enhanced interfacial bonding forms a more stable microstructure in the film and improves the overall performance of the film; during the pretreatment process, the coupling agent not only promotes the bonding of shallow etching particles and deep etching particles, but also may help to disperse other functional additives on the combined particles, further improving the uniformity and performance stability of the film.
[0086] The combined particles formed by pretreatment form a unique microstructure in the film and can be distributed at different levels, thereby forming a multifunctional gradient structure in the film. Due to the formation of combined particles and the improvement of additive dispersibility, the comprehensive performance of the film is significantly improved, especially when the performance of shallow etching particles and deep etching particles can complement each other, this improvement effect will be more obvious;
[0087] The pretreatment process reduces agglomeration and sedimentation in the subsequent reaction process, thereby improving the stability of the film preparation process, reducing the scrap rate in the production process and improving production efficiency;
[0088] The inner layer is completely composed of macromolecular organic matter, which can better wrap the cigarette box during heat sealing, improve the sealing and softness; the combination of unetched tourmaline powder and etched small-particle tourmaline powder complements each other in particle size, forming a more uniform distribution and more comprehensive functional coverage in the middle layer of the cigarette film; large-particle tourmaline powder can enhance the toughness, strength and heat insulation ability of the film, while small-particle etched tourmaline powder can resist bacteria, deodorize, and prevent far-infrared radiation, which can evenly distribute the heat inside the cigarette and improve the combustion efficiency of the cigarette;
[0089] Tourmaline powders with different etching depths have different surface structures and properties. When used in combination, their respective advantages are combined to make up for the shortcomings of tourmaline powder with a single etching depth. For example, tourmaline powder with shallow etching may maintain good mechanical strength, while tourmaline powder with deep etching can significantly improve the anchoring effect of additives. After the combination, the film has good mechanical properties and can significantly improve other key properties (such as friction, antistatic properties, etc.).
[0090] Tourmaline powder with different etching depths may produce a synergistic effect in the film, further improving the overall performance of the film; for example, shallowly etched tourmaline powder acts as a mechanical support point, while deeply etched tourmaline powder acts more as an anchor and dispersion of functional additives. The combination of the two optimizes the mechanical and functional properties of the film.
[0091] The combination of tourmaline powders with different etching depths provides more flexibility and adjustability for the film preparation process; manufacturers can choose the appropriate tourmaline powder combination ratio according to specific application requirements and product specifications to achieve the best performance balance;
[0092] By combining tourmaline powder with different etching depths, the comprehensive properties of heat-sealable BOPP film for cigarettes are significantly improved, including mechanical properties, heat-seal properties, smoothness, antistatic properties, optical properties, etc., making the film more adaptable and more competitive in application fields such as cigarette packaging;
[0093] Under the premise of ensuring the performance of the film, by reasonably selecting the etching depth and combination ratio of tourmaline powder, the raw material cost and production efficiency can be optimized; the production cost of the film can be reduced and the economic benefits can be improved.
[0094] The presence of the microporous structure enables 1,6-hexanediol diglycidyl ether (as a coupling agent) to better penetrate into the micropores, thereby effectively "anchoring" macromolecules such as trimethylsiloxyamino-terminated polydimethylsiloxane and hydroxyl-terminated methyl-3,3,3-trifluoropropyl polysiloxane on the etched crystal tourmaline powder. This anchoring effect significantly improves the dispersion uniformity of these additives in the polymer matrix, avoiding the problem of easy migration and precipitation of traditional small molecule additives.
[0095] Due to the uniform anchoring of macromolecular additives on tourmaline powder, the surface friction coefficient of the film is significantly reduced, which not only improves the smoothness of the film, but also reduces the friction during the packaging process, which is conducive to high-speed packaging, and also reduces the wear and noise during the packaging process;
[0096] The synergistic effect of the microporous structure and macromolecular additives also enhances the antistatic performance of the film. Due to the uniform distribution of macromolecular additives on the tourmaline powder, a durable antistatic layer can be formed on the surface of the film, effectively preventing static electricity accumulation and protecting the product from static electricity damage.
[0097] The microporous structure improves the heat-sealing and mechanical properties of the film. By optimizing the distribution of additives, the film can melt more evenly during the heat-sealing process to form a strong seal. At the same time, the microporous structure can also enhance the mechanical strength of the film to a certain extent, and improve its tear resistance, wear resistance and other properties.
[0098] At the microscopic level, the etching process mainly involves the following key steps:
[0099] Concentrated sulfuric acid etching: Concentrated sulfuric acid etches the surface of crystalline tourmaline powder to form a large number of micropores. The size, shape and distribution of these micropores depend on the concentration of sulfuric acid, reaction time and temperature.
[0100] Coupling agent infiltration: 1,6-hexanediol diglycidyl ether, as a coupling agent, enters the micropores of tourmaline powder through infiltration. This infiltration enhances the interaction between tourmaline powder and subsequent additives.
[0101] Macromolecular anchoring: Macromolecular additives such as trimethylsiloxyamino-terminated polydimethylsiloxane and hydroxyl-terminated methyl-3,3,3-trifluoropropyl polysiloxane are combined with the microporous structure of tourmaline powder through coupling agents to form a stable anchoring effect. This anchoring effect ensures the uniform distribution and durability of the additives in the film.
[0102] Polymer matrix melt blending: During the melt blending process, the etched crystal tourmaline powder and its anchored macromolecular additives are fully mixed with the matrix materials such as polypropylene. Due to the uniform distribution of the additives on the tourmaline powder, their dispersion in the film is significantly improved, thereby improving the various properties of the film.
[0103] In summary, the microporous structure of etched crystalline tourmaline powder plays a vital role in the preparation of heat-sealable BOPP film for cigarettes. By optimizing the formation conditions of the microporous structure and the anchoring effect of additives, the key indicators of the film, such as friction performance, antistatic performance, heat sealing performance and mechanical properties, can be significantly improved.
[0104] Embodiment 4
[0105] Embodiment 3 not only improves its various capabilities but also improves the stability of the film by etching tourmaline and stone combination at different etching depths. In order to improve its various adaptability, further improvements are made on the basis of embodiment 3.
[0106] The particle size of tourmaline powder is divided into three levels, specifically:
[0107] Fine particle size (<1μm): suitable for filling in the fine structure of the film to improve the dispersion of additives and the uniformity of the film;
[0108] Medium particle size (1-5 μm): as the main reinforcement and etching component, balancing mechanical properties and functional properties;
[0109] Coarse particle size (5-10 μm): used to improve the rigidity and wear resistance of the film;
[0110] During the etching process of tourmaline powder with different particle sizes, pressure is applied, and by controlling the pressure and etching time, etched tourmaline powder with different etching depths is obtained, specifically including:
[0111] Shallow etching (0-0.1μm)
[0112] Impact on thin film processing: Due to the shallow etching depth, the change in the surface structure of tourmaline powder is small, which is not enough to significantly enhance the anchoring effect of additives.
[0113] The film performance is not significantly improved, but the original physical and chemical stability of tourmaline powder can still be maintained.
[0114] Moderate etching (0.1-0.5μm)
[0115] Impact on film processing: The etching depth is moderate, which is conducive to better penetration and anchoring of coupling agents and macromolecular additives on the surface of tourmaline powder, improving the dispersion uniformity of additives, and improving the friction coefficient, antistatic properties, heat sealing properties and mechanical properties of the film;
[0116] Deep etching (0.5-1.0μm)
[0117] Impact on film processing: Deeper etching allows more microporous structures to form on the surface of tourmaline powder, further enhancing the anchoring effect of additives;
[0118] The invention has the following technical effects or advantages:
[0119] Fine particle size (<1μm) improves the dispersion of additives and the uniformity of the film, and is suitable for film applications that require high uniformity and fine structure;
[0120] Medium particle size (1-5μm), as the main reinforcement and etching component, balances mechanical properties and functional properties, suitable for thin film applications that require both strength and function;
[0121] Coarse particle size (5-10μm) improves the rigidity and wear resistance of the film, and is suitable for film applications that require high rigidity and wear resistance, such as packaging materials, industrial coatings, etc.
[0122] Pressurization will enhance the penetration of sulfuric acid solution into the tourmaline surface, making it easier for sulfuric acid to penetrate deep into the tourmaline for etching; at the same time, extending the treatment time means that sulfuric acid has more time to react with tourmaline, further increasing the degree of etching. Therefore, pressurization and extended treatment time usually lead to an increase in the depth of voids (micropores).
[0123] Changes in the tourmaline surface: As the etching depth increases, the roughness of the tourmaline surface will also increase accordingly. Deeper etching means more substances are dissolved, leaving more unevenness on the tourmaline surface.
[0124] Changes in the number and distribution of micropores: Pressurization and extended treatment time not only increase the depth of micropores, but may also increase the number of micropores. At the same time, the distribution of micropores may also become more dense and irregular, depending on the degree of pressurization and the length of treatment time;
[0125] Changes in surface chemical properties: The pickling process will change the chemical properties of the tourmaline surface, such as increasing the number of surface hydroxyl groups or introducing other functional groups. These changes may affect the interaction of tourmaline with other additives (such as coupling agents and macromolecular polymers);
[0126] Different applications can be achieved through different combinations. For example, the combination of fine particle size and shallow etching: maintains the physical and chemical stability of tourmaline powder, which is suitable for applications that do not require high film performance but need to maintain good stability; the combination of medium particle size and medium etching improves the dispersion uniformity of additives, improves the friction coefficient, antistatic properties, heat sealing properties and mechanical properties of the film, and is suitable for film applications that require comprehensive performance improvement, such as electronic product packaging, food packaging, etc.; the combination of coarse particle size and deep etching forms more microporous structures, enhances the anchoring effect of additives, and significantly improves the rigidity and wear resistance of the film. It is suitable for film applications with extremely high requirements for rigidity and wear resistance, such as industrial protective coatings, high-performance packaging materials, etc.
[0127] The following is a performance test of the films obtained from Examples 1 to 4 of the present invention and the comparative example (the heat-sealable BOPP film for cigarettes prepared by Application No. CN202110419090.8) (the thickness of the surface layer and the inner layer of each film is 1um, and the thickness of the core layer is 20um), and the test results are shown in Table 1;
[0128] Among them, the static / dynamic friction coefficient at room temperature and the static / dynamic friction coefficient at 50℃ are the friction coefficients between the surface layers, tested in accordance with DIN EN ISO 8295 (2004-10); the surface resistance after 5 days and the surface resistance after 15 days are the surface resistances measured after being washed, placed for 5 days and 15 days and dried, respectively, and tested in accordance with GB / T1410-78.
[0129] Table 1 Performance test of Examples 1 to 4 and Comparative Examples
[0130]
[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A heat-sealable BOPP film for cigarettes, characterized in that: Specifically, it is made by direct co-extrusion of the three-layer structure of outer layer, middle layer and inner layer; Wherein, the outer layer is made of raw materials including the following parts by weight: 38-45 parts of polypropylene, 20-26 parts of propylene-ethylene copolymer, 25-32 parts of ethylene-methyl acrylate copolymer, 7.5-9 parts of etched crystal tourmaline powder, 1.5-2 parts of 1,6-hexanediol diglycidyl ether, 4.6-5.2 parts of a mixture of trimethylsiloxyamino-terminated polydimethylsiloxane and hydroxyl-terminated methyl-3,3,3-trifluoropropyl polysiloxane, 3-4.5 parts of polytetrafluoroethylene etched polyethylene wax powder, and 2-3 parts of nano silicon dioxide; the etched crystal tourmaline powder is prepared by etching crystal tourmaline powder; the particle size of the crystal tourmaline powder is 20-100nm; The interlayer is made of the following raw materials in parts by weight: 80-90 parts of polypropylene, 12-17 parts of propylene-ethylene copolymer, 7-9 parts of ethylene-methyl acrylate copolymer, 0.5-1 parts of 1,6-hexanediol diglycidyl ether, 2-3 parts of nano silicon dioxide, 5-6 parts of shallowly etched crystalline tourmaline powder, and 5-6 parts of deeply etched crystalline tourmaline powder; The inner layer is made of the following raw materials in parts by weight: 38-45 parts of polypropylene, 20-26 parts of propylene-ethylene copolymer, 25-32 parts of ethylene-methyl acrylate copolymer; The thickness of the outer layer and the inner layer is 0.8-1.2 μm, and the thickness of the interlayer is 18-22 μm; The method for preparing the above BOPP film comprises the following steps: S1. Prepare etched crystalline tourmaline powder, specifically: add concentrated sulfuric acid in an amount of 1.2-1.5 times the mass of the crystalline tourmaline powder to the crystalline tourmaline powder, stir and react for 10-15 minutes, control the concentration of sulfuric acid to be greater than 95% during the entire reaction process, and control the temperature to be 50° C. during the entire reaction process; filter after the reaction is completed, wash the filter residue with water, and dry it in turn to obtain the etched crystalline tourmaline powder; The preparation method of shallow etched crystalline tourmaline powder is specifically as follows: adding concentrated sulfuric acid of 1.2-1.5 times the mass of the crystalline tourmaline powder to the crystalline tourmaline powder, stirring and reacting for 0.5-3 minutes, the concentration of the sulfuric acid is greater than 95%, and the temperature during the reaction is 50°C; The preparation method of deep-etched crystal tourmaline powder is specifically as follows: adding concentrated sulfuric acid of 1.2-1.5 times the mass of the crystal tourmaline powder to the crystal tourmaline powder, stirring and reacting for 10-25 minutes, wherein the concentration of the sulfuric acid is greater than 95%, and the temperature during the reaction is 50° C.; filtering after the reaction is completed, washing the filter residue with water and drying it in turn, to obtain the etched crystal tourmaline powder; The shallow etched crystal tourmaline powder and the deep etched crystal tourmaline powder are also pre-treated before being added to the interlayer, and the shallow etched crystal tourmaline powder and the deep etched crystal tourmaline powder are mixed and 1,6-hexanediol diglycidyl ether is added; S2, preparing a mixture of the outer layer raw materials, specifically, drying the etched crystal tourmaline powder until the moisture content is less than 0.2wt%, then mixing the dried etched crystal tourmaline powder with 1,6-hexanediol diglycidyl ether, and placing it at 52-60°C and 2-3 standard atmospheric pressures for 6-10 hours; and then mixing it with a mixture of trimethylsiloxyamino-terminated polydimethylsiloxane and hydroxyl-terminated methyl-3,3,3-trifluoropropyl polysiloxane to obtain an etched crystal tourmaline powder premix; S3, preparing melts of each layer: uniformly mixing the etched crystal tourmaline powder premix with other raw materials of the outer layer, melting and plasticizing, to form an outer layer melt; The raw materials of the interlayer and the inner layer are mixed evenly, melted and plasticized to form an interlayer melt and an inner layer melt; S4, the interlayer melt, the outer layer melt and the inner layer melt are extruded after being merged at the die head, and are rapidly cooled by a quenching roller and a water tank to form a solid casting sheet; then longitudinal stretching and transverse stretching are performed; and cooling and shaping treatment is immediately performed after stretching; S5, sequentially undergoing online thickness measurement, edge material cutting, automatic winding, aging treatment, and finally slitting to obtain the finished product, the heat-sealed BOPP film for cigarettes.
Citation Information
Patent Citations
A heat-sealable BOPP film for cigarettes and its preparation method
CN113059880B
Preparation process for negative-ion material
CN109705427A
heat-sealing BOPP film for cigarettes and preparation method of BOPP film
CN113059880A